(3SQ GdCSQGQ aj GdcjejGAs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf EYde Cfi LeYJ gPG GdcJGH ef SQGFQ GdCYeGd ddUfYI djchf EeGekG jbJOi Hg , hOSJhQkG jQLY Edjg s
(3BNQgG (B:s
(3hJYGgO GdNfOb hGdMaQI djVY HPdc eG CfMd hGdMeO ddg GdZGaQ GdcQje GdKfGA hGdUdGI Ydi eMeO SjO GdCHQGQG heSfO GdCNHGQ JSdjekG cKjQkG Bejf s
(3HgG fXGe GdJYbjHIs
(3Ydb GdfGSN HYOgG ahGFO hJbY gPg GdahGFO ai (B8 (3hQbGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B103s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(700) s
Keywords: (3GdcjejGA h GdWHjYjGJs